The Effects of Service Quality and Sales Promotion on Customer Loyalty through Word-of-Mouth as Intervening Variable - Linawati, Linawati; Ardyan, Elia (Review of Management and Entrepreneurship, 2025)
This research aims to determine the influence of service quality and sales promotions on customer loyalty at Matahari Kapasan Store through word of mouth as an intervening variable. The study focuses on a family business operating in the wholesale clothing manufacturing and supplier industry. The study employs a quantitative research method with Structural Equation Modeling for data analysis. The population in this study consists of loyal customers. The sampling technique used in this research was purposive sampling with a sample size of 84 respondents. Primary data used in this research was obtained through a questionnaire using a Likert scale. The results indicate that word of mouth plays a significant role as an intervening variable in influencing customer loyalty. The results of this study highlight the novelty of exposure implications, showing that the role of word of mouth as an intervening variable has a meaningful impact on customer loyalty in terms of service quality and sales promotion.